Crystal structure of chalcogenides R’xR’’yR’’’zPbSi2S8 (R’ – La, R’’ – Tb, R’’’ – Er) - Marchuk, O.V.; Smitiukh, O.V.; Prots, Yu.; Fedorchuk, A.O. (Physics and Chemistry of Solid State, 2021)
The chalcogenides LaxTbyErzPbSi2S8 were obtained by synthesizing the elementary components in vacuum quartz containers at 1320 K. The synthesized alloys were homogenized by annealing at 770 K during 500 hours. The cell parameters of synthesized sulfides are: a = 0,89576(3) nm, c = 2,65646(8) nm – La1,2Tb0,4Er0,4PbSi2S8; a = 0,89209(1) nm, c = 2,63466(5) nm – La0,9Tb0,2Er0,9PbSi2S8; a = 0,89002(3) nm, c = 2,62714(7) nm – La0,67Tb0,67Er0,67PbSi2S8; a = 0,88993(1) nm, c = 2,62973(4) nm – La0,6Tb1,2Er0,2PbSi2S8; a = 0,885161(7) nm, c = 2,60445(3) nm – La0,2Tb0,9Er0,9PbSi2S8 respectively. The atoms of statistical mixture (La,Tb,Er,Pb) occupy the site 18e (x y 1/4), and the atoms of Si occupy the site 12c (1/3 2/3 z) in the structure of the obtained chalcogenides. Coordinating polyhedra of atoms of the statistical mixture (La, Tb, Er, Pb) are trigonal prism with two additional atoms (CN = 8), and the atoms of Si occupying the crystallographic point system 12c describes with the tetrahedron. According to the results of the experiment, the synthesized chalcogenides crystallize in the structure type of La2PbSi2S8 (hR26,167). The structure of La2PbSi2S8 is described by using the theory of second anion coordination (SAC).